Message strategies in smartphone patent battles: ownership and innovation capability. Issue 3 (1st August 2016) - Kim, Ji Young
Abstract : Purpose: This study aims to examine the effects of message attributes on public opinion in regards to corporate reputation and communication intention. Design/methodology/approach: It conducted a 2x 2 between-subject factorial experiment, manipulating media messages in terms of which company owns the patents, and the level of innovation emphasized through the companies' marketing communication efforts. Findings: The two-way ANOVA results showed that, for Samsung, the main effects of the two independent variables (ownership and innovation) were found on the perceived corporate reputation; while only a main effect of innovation capability attribute was found on the perceived secondary communication intention for Apple. Research limitations/implications: One main theoretical contribution of this current study is the exploration of the attribute-level of agenda setting in the context of a business communication setting with an experimental study. Practical implications: This result would suggest that practitioners should focus on their marketing strategies as well when they are involved in a lawsuit case. When a company loses a lawsuit, the company's perceived reputation is dropped; however, the dropping gap can be reduced when the company has been portrayed as an innovative leader in the market. Originality/value: This is an empirical experiment exploring a causal effect of message attributes on public opinion. The two companies in this study are the industry leaders and the case is current.